Tissue-specific expression of the rat alpha 2u globulin gene family. - MacInnes, J I (1986)
The rat alpha 2u globulin gene family encodes approximately 20 low-molecular-weight (20,000) proteins with pIs ranging from 4.5 to 7.9. alpha 2u globulin protein isoforms were detected in the liver and in the submaxillary, lachrymal, preputial, and mammary glands of Sprague-Dawley rats. The hormonal and developmental regulation of alpha 2u globulin synthesis in each of these tissues was unique, and it appears that different alpha 2u gene sets were transcribed in the various tissues.